Folate Transporters Are Found Throughout the Colon of Humans and Their mRNA Expression Appears to Be Unaffected by Low Dose Folic Acid Supplementation. (7th June 2021) - Farrell, Colleen; Khanna, Siya; Hoque, Md. Tozammel; Basset, Nancy; Plaga, Aneta; Syed, Ishba; Aufreiter, Susanne; Bendayan, Reina; Kandel, Gabor; Kim, Young-In; O'Connor, Deborah
Abstract: Objectives: A large depot of folate resides in the colon and can exceed dietary intake. Little is known about the capacity of the colon to absorb folate. We aimed to determine the expression of key folate transporters, reduced folate carrier (RFC) and proton-coupled folate transporter (PCFT), throughout the colon of healthy adults and the impact of low dose folic acid (FA) supplementation. Methods: In this 16 wk open-labelled randomized control trial, healthy adults (n = 25) from a colonoscopy waiting list were randomized to receive daily a multivitamin plus a 400 μg FA (400FA, n = 12) or no FA supplement (0FA, n = 13). Subjects were provided with low FA bread and pasta and instructions how to follow a low FA containing diet. Six 24-hr diet recalls were administered throughout the study and blood samples were collected at baseline, 8 and 16 wk. At colonoscopy (16 wk), 4 tissue biopsies were collected from the terminal ileum, cecum, ascending and descending colon. Blood folates were determined by microbial assay; mRNA levels of folate transporters were assessed using qPCR. Results: One subject was removed from analysis due to missing data (0FA). No group differences in age, sex, BMI, dietary intake, vitamin B12, red blood cell (RBC) and plasma folate levels at baseline were observed. Mean ± SD FA supplement adherence was 92 ± 12% and 96 ± 9% at 8 and 16 wk, respectively. Subjects in the 400FA group had higher total folate intake ( P  < 0.05) and higher RBC and plasma folate levels ( P  < 0.01) at 8 and 16 wk compared to 0FA subjects. RBC values at 16 wk were 1764 ± 636 and 865 ± 190 nmol/L in the 400FA and 0FA group, respectively. RFC and PCFT were detected in terminal ileum and colon biopsies (n = 96) and their mRNA levels in each section did not differ between groups. However, expression of RFC was markedly higher than PCFT across all biopsy sections ( P  < 0.05) and highest in the terminal ileum, compared to the cecum, ascending and descending colon in both groups ( P  < 0.05). Conclusions: We demonstrated expression of folate transporters, RFC and PCFT, throughout the human colon suggesting their potential contribution to overall folate absorption. mRNA expressions were not affected by a low dose FA supplement. A deeper understanding of how FA and folate status affect colonic transporter regulation may inform future revisions of folate intake recommendations. Funding Sources: Natural Sciences and Engineering Research Council.